Early Health Technology Assessment during Nonalcoholic Steatohepatitis Drug Development: A Two-Round, Cross-Country, Multicriteria Decision Analysis. (August 2020) - Angelis, Aris; Thursz, Mark; Ratziu, Vlad; O'Brien, Alastair; Serfaty, Lawrence; Canbay, Ali; Schiefke, Ingolf; Costa, Joao Bana e; Lecomte, Pascal; Kanavos, Panos
Background. The assessment of value along the clinical development of new biopharmaceutical compounds is a challenging task. Complex and uncertain evidence has to be analyzed, considering a multitude of value preferences from different stakeholders.Objective. To investigate the use of multicriteria decision analysis (MCDA) to support decision making during drug development while considering payer and health technology assessment (HTA) value concerns, by applying the Advance Value Framework in nonalcoholic steatohepatitis (NASH) and testing for the consistency of the results.Design. A multiattribute value theory methodology was applied and 2 rounds of decision conferences (DCs) were organized in 3 countries (England, France, and Germany), with the participation of national key experts and stakeholders using the MACBETH questioning protocol and algorithm. A total of 51 health care professionals, patient advocates, and methodologists, including (ex-) committee members or assessors from national HTA bodies, participated in 6 DCs in the study countries.Target Population. NASH patients in fibrosis stages F2 to 3 were considered.Interventions. The value of a hypothetical product profile was assessed against 3 compounds under development using their phase 2 results.Outcome Measures. DC participants' value preferences were elicited involving criteria selection, options scoring, and criteria weighting.Results. Highly consistent valuation rankings were observed in all DCs, always favoring the same compound. Highly consistent rankings of criteria clusters were observed, favoring therapeutic benefit criteria, followed by safety profile and innovation level criteria.Limitations. There was a lack of comparative treatment effects, early evidence on surrogate endpoints was used, and stakeholder representativeness was limited in some DCs.Conclusions. The use of MCDA is promising in supporting early HTA, illustrating high consistency in results across countries and between study rounds.